Consumer perception, knowledge, and uses of cannabidiol - Nguyen Cambrey PharmD; Moeller Karen E. PharmD; McGuire Michael PharmD; Melton Brittany L. PharmD, PhD (American Association of Psychiatric Pharmacists, 2023)
Introduction The legalization of cannabidiol (CBD) across the United States, in varying degrees, has made CBD easily accessible to consumers for complementary and medical purposes. However, there is a paucity of scientific evidence on the benefits and risks of commercially available CBD. In the literature, 2 studies have gathered consumer perceptions and attitudes on cannabis products, specifically CBD, using survey-based questionnaires. This study aimed to build on the aforementioned studies in obtaining consumer perception and knowledge of CBD products using a national survey-based questionnaire. Methods Respondents were recruited through an anonymous, nationwide, online survey administered through Qualtrics in the United States from March 28 to April 30, 2021. The survey consisted of demographics, perceived efficacy and safety of CBD, and resources to obtain CBD information. The survey responses were reported using descriptive statistics along with median and interquartile range for the Likert portion. Results A total of 1158 respondents accessed the survey. The median age was 43 and 50% of respondents were female. The uses for CBD included neurological disorders, pulmonary conditions, gastrointestinal disorders, and chronic pain. The most commonly reported safety concern related to taking CBD was anxiety. Participants agreed that CBD is safe when used responsibly for medical use, and social media was the main source used to obtain information about CBD. Discussion Respondents who used CBD for a condition thought it was helpful; however, most of the adverse effects were rated as moderate to severe, requiring medical attention from a health care professional, hospital, or emergency room visit.